The concept of Functions in Secondary School Textbooks: The Hybrid Approach - Rossi, Laura Susana (2020)
This work is part of a broader investigation, in which we use the Theory of Conceptual Fields to analyse the meaning of function that emerges from the way high school books teach it. We analysed 24 high school books published between 1953 and 2010. In particular, we described the characteristics of the books that we classify into an approach we call a hybrid. This classification focuses on the identification of the representation systems used, the meaning and the situation. The results show that this approach, although it strives for a process of pragmatic knowledge elaboration, does not promote a true study of the problem, before its formalization. Rather, the problem works like a school task whose functionality is linked to the definitions.